Persepsi Dukungan Organisasional dan Kualitas Hidup Kerja Terhadap Organizational Citizenship Behavior dengan Work Engagement Sebagai Variabel Pemediasi - Arik Nur Cahyo; Indra Prasetyo; Woro Utari (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2023)
The purpose of this study is to describe Organizational Citizenship Behavior, work engagement, organizational support and quality of work life of employees at the Department of Public Works, Bina Marga and Spatial Planning, Bojonegoro Regency. And to analyze the effect of organizational support and quality of work life on Organizational Citizenship Behavior through work engagement. This type of research uses explanatory research with a quantitative research approach. The population in this study were all employees of the Department of Public Works, Highways and Spatial Planning, Bojonegoro Regency, totaling 52 people and the sample was also 52 people using a census sampling technique. Methods of data collection using questionnaires and documentation. Methods of data analysis using SEM with PLS. The results showed Organizational Citizenship Behavior, work engagement, organizational support and quality of work life of employees in the high category. Organizational support for work engagement has a positive but not significant effect. Quality of work life has a significant effect on work engagement. Organizational support, quality of work life and work engagement have a significant effect on OCB. Organizational support for OCB through work engagement has an insignificant effect, quality of work life for OCB through work engagement has a significant effect.